Pediatric Nuclear Medicine Examinations and Subsequent Risk of Neoplasm: A Nationwide Population-Based Cohort Study - Yuan, Mei-Kang; Chang, Shih-Chieh; Yuan, Mei-Chun; Foo, Ning-Ping; Chan, Shan-Ho; Wang, Shyh-Yau; Lin, Cheng-Li; Hsu, Chung-Y.; Kao, Chia-Hung (Frontiers in Medicine, 2021)
OBJECTIVE: To evaluate the association between radiation exposure from repeated nuclear medicine (NM) examinations and the subsequent risk of neoplasm in pediatric patients. METHODS: From 2000 to 2017, participants under 18 years of age who underwent NM scanning were identified using the Health and Welfare Data Science Center (HWDC) dataset, which was extracted from the Taiwan National Health Insurance Research Database (NHIRD). Both the exposed cohort and unexposed subjects were followed up with until the presence of any malignancy arose, including malignant brain, lymphoid and hematopoietic tumors and benign brain or other central nervous tumors. RESULTS: There were 35,292 patients in the exposed cohort and 141,152 matched subjects in the nonexposed group. The exposed cohort had an overall higher IR (IR: incidence rate, per 100 000 person-years) of any malignancy and benign central nervous tumor than the nonexposed group (IR, 16.9 vs. 1.54; adjusted hazard ratio [HR], 10.9; 95% CI, 6.53–18.2). Further stratifying the number of NM examinations into 1-2, 3-4, and 5 or more times revealed that the IR of pediatric neoplasms increased gradually with the increased frequency of NM examinations (IR, 11.5; adjusted HR, 7.5; 95% CI, 4.29–13.1; IR, 25.8; adjusted HR, 15.9; 95% CI, 7.00–36.1; IR, 93.8; adjusted HR, 56.4; 95% CI, 28.8–110.3). CONCLUSION: NM examination is significantly associated with a higher risk of pediatric neoplasms, according to our population-based data. Thorough radiation protection and dose reduction in pediatric NM procedures should be an issue of concern.